(untitled) (The Review of Diabetic Studies, 2025)
Background: Healthcare systems face increasing demands, necessitating enhanced clinical decision-making in nursing. Artificial intelligence (AI) offers potential as a transformative tool to support nursing judgment by analyzing clinical data, identifying patterns, and providing evidence-informed insights. However, its integration into practice requires examination of nurses’ perceptions and experiences. Methods: A quantitative cross-sectional study was conducted with 200 registered nurses. A structured questionnaire, distributed via electronic and paper formats, assessed demographic characteristics, exposure to AI technologies, and perceptions of AI’s impact on decision-making and diagnostic support. Descriptive and inferential statistics were used for data analysis. Results: Most participants (77.5%) reported moderate to high exposure to AI. A significant majority (77.5%) agreed or strongly agreed that AI positively influences nursing decision-making, and 77.5% rated AI as effective or very effective in diagnostic support. A statistically significant association (p < 0.05) was found between higher AI exposure and greater confidence in clinical decision-making. Conclusion: AI is perceived positively by nurses as a supportive tool that enhances decision-making confidence and diagnostic accuracy. Successful integration requires targeted education, ethical governance, and nurse involvement in technology development to ensure AI augments patient-centered care while preserving professional autonomy.